La cultura financiera y su incidencia en la economía familiar de los habitantes del cantón Macará. - Tandazo Ocampos, Luis Gustavo (2022)
Financial education and financial culture are essential in people's daily lives since it allows them to improve their skills and knowledge about the effective management of their money and, thus, improve their economic and financial stability. The general objective of this research was to determine how financial culture affects the economy of families from Macara. In order to do this, it was necessary to diagnose the families’ economic situation and their financial culture. The methodology applied in this research comprises a mixed-method (quantitative and qualitative research), as well as a descriptive approach and fieldwork. The research instrument to collect data was a questionnaire, which was applied to a sample of 377 families from Macara. The results obtained indicated that a large part of the families did not have a culture of saving money. This happens due to the lack of knowledge about financial education, which results in the inadequate management of the participants’ finances. By using Chi-square statistical test, the main findings showed that there was not a significant relationship between financial culture and savings, level of indebtedness, and the budget for family expenses, which means that there was no correlation. In addition, a guide about financial education and the necessary instruments for saving, budgeting, and financing was proposed. Finally, it was concluded that financial culture facilitates well-founded decision-making, which turns financial education into a very efficient tool to protect thrifty people and investors’ money and increase the stability and development of the economic and financial system